2023
DOI: 10.1177/10748407231167545
|View full text |Cite
|
Sign up to set email alerts
|

When Family Life Contributes to Cancer Caregiver Burden in Palliative Care

Abstract: The difficulties of caring for a family member with advanced cancer are well documented. Support from a caregiver’s social network—especially other family—is vital to reducing caregiver burden and psychological distress. However, the family environment is not always supportive as reports of family conflict and dissatisfaction with support are common. Despite knowing that family relationships are complex, little is known about the types of family stress that caregivers of advanced cancer patients face in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…al highlighted four main themes of familial distress in the families of a caregiver: failed support, relational tensions, denial, and additional care work. 8 As such, dysfunctional family dynamics potentially explain why stress and subsequent mental health issues increased in our sample of caregivers.…”
Section: Discussionmentioning
confidence: 92%
“…al highlighted four main themes of familial distress in the families of a caregiver: failed support, relational tensions, denial, and additional care work. 8 As such, dysfunctional family dynamics potentially explain why stress and subsequent mental health issues increased in our sample of caregivers.…”
Section: Discussionmentioning
confidence: 92%
“…However, the toll on these unsupported caregivers' physical health suggests that their need is signi cant. A recent qualitative study reported cancer caregivers implicitly expect other family members to offer support without having to directly ask [37].…”
Section: Discussionmentioning
confidence: 99%
“… 9 Caregiver burden is a multidimensional concept related to the physical symptoms, psychological distress, impaired social relationships, spiritual distress and financial strain that arise from caregivers. 10 11 In the context of advanced lung cancer, as psychological distress and associated fatigue interference affect patients’ functioning, family caregivers of lung cancer patients are required to spend longer time performing care duties for patients while neglecting their own vital activities. 12 Coping with demanding role changes and increased caregiving burden can significantly disrupt daily routines, impact caregivers’ mental and physical health, thus influencing their sense of meaning in life.…”
Section: Introductionmentioning
confidence: 99%